RELATIONSHIPS AMONG SELF-ESTEEM, MOTIVATION, COMMUNICATIVE APPROACH, AND SPEAKING ACHIEVEMENT OF THE STUDENTS - Sri Endah Kusmartini (HOLISTICS, 2020)
Abstract: This research is aimed to find out the relationships among self-esteem, school motivation,communicative approach, and speaking achievement of the students. The data were collected throughquestionnaires and speaking test. The data were analyzed by using Pearson Product Moment CoefficientCorrelation and Multiple Regression Linear. The results show that there is a positive and significantrelationship between self-esteem and speaking achievement of the students (r = 0.474); there is a positiveand significant relationship between school motivation and speaking achievement of the students (r =0.561); there is positive and significant relationship between communicative approach and speakingachievement (r = 0.679); there is a positive and significant relationship between self-esteem and schoolmotivation (r = 0.567); there is a positive and significant relationship between school motivation andcommunicative approach (r = 0.510); there is a positive and significant relationship between self-esteemand communicative approach (r = 0.590); there is a positive relationship between self-esteem added toschool motivation and communicative approach towards speaking achievement (R = 0.723).Simultaneously, there is a significant influence of independent variables towards dependent variable ofthe research. The contribution of self-esteem, school motivation, and communicative approach towardsspeaking achievement of the students is 45.5%.